Linguacultural Features of English and Uzbek Paremias - Makhsudova Nilufar Abdurasulovna (Goodwood Publishing, 2026)
Purpose: This study examines English and Uzbek proverbs to identify shared and distinct features of their spiritual worlds and national identities. Research Methodology: A descriptive method was first used to analyze the semantic characteristics of proverbs in both languages. A comparative typological approach followed to highlight universal and culturally specific features. Additionally, the linguacultural method was applied to interpret cultural concepts embedded in the proverbs. Results: The study supports Humboldt’s theory of inner and outer language forms. While both languages express universal truths, they reflect distinct cultural contexts English proverbs often emphasize individualism, while Uzbek proverbs prioritize collectivism. These differences demonstrate how a nation’s worldview shapes its expression of wisdom. Conclusions: Proverbs preserve a nation’s unique spiritual and social essence. English proverbs emphasize individualism and pragmatism, while Uzbek proverbs highlight collective harmony, respect for lineage, and hospitality. Limitations: This study is limited to the semantic and structural analysis of paroemias, leaving the phonetic and rhythmic aspects of the outer form for future investigation. Expanding the scope to include regional dialects would provide an even deeper look into these linguacultural codes. Contributions: This study contributes to paremiological studies by providing a comparative framework for analysing how national identity is encoded in folk wisdom. Specifically, it offers a practical foundation for compiling a thematic dictionary of proverbs that goes beyond literal translation to categorize proverbs by their shared moral and cultural values.